2011
DOI: 10.1007/s10008-011-1572-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in structure and Li+-ion migration in argyrodite-type Li6PS5X (X = Cl, Br, I) solid electrolytes

Abstract: All-solid-state rechargeable lithium-ion batteries (AS-LIBs) are attractive power sources for electrochemical applications due to their potentiality in improving safety and stability over conventional batteries with liquid electrolytes. Finding a solid electrolyte with high ionic conductivity and compatibility with other battery components is a key factor in raising the performance of AS-LIBs. In this work, we prepare argyrodite-type Li 6 PS 5 X (X = Cl, Br, I) using mechanical milling followed by annealing. X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
219
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(239 citation statements)
references
References 19 publications
17
219
2
1
Order By: Relevance
“…The lattice parameters of Li 6 PS 5 Cl in the samples annealed at 400–600 °C have similar values as shown in Figure 3b, comparable to previously reported values. 12 Increasing the annealing temperature to 550 °C leads to a clear decrease in the background of the XRD patterns (seen in Figure 1), indicating that the amorphous fraction decreases and the crystalline fraction increases. In addition, the linewidth of the reflections is the smallest at 550 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lattice parameters of Li 6 PS 5 Cl in the samples annealed at 400–600 °C have similar values as shown in Figure 3b, comparable to previously reported values. 12 Increasing the annealing temperature to 550 °C leads to a clear decrease in the background of the XRD patterns (seen in Figure 1), indicating that the amorphous fraction decreases and the crystalline fraction increases. In addition, the linewidth of the reflections is the smallest at 550 °C.…”
Section: Resultsmentioning
confidence: 99%
“…ND is in particular important for determining the Li-ion positions and the Cl/S distribution over the 4a and 4c sites which has been shown to be a key parameter for the ionic conductivity. 12,18,21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li-argyrodites,L i 6 PS 5 X( X= Cl, Br), fall into this latter family and are easily synthesized using inexpensive precursors.T heir cubic crystal structures F " 43m ÀÁ are comprised of PS 4 3À tetrahedra, with isolated S 2À and X À ions disordered over the 4 a and 4 c Wyckoff sites in the lattice,a nd Li + ion sites that form cagelike Frank-Kasper polyhedra around the anions. [7] While room-temperature Li-ion conductivities initially reported for the Cl (1.9 mS cm À1 ) [8] and Br phases (0.7 mS cm À1 ), [9] were within practical ranges,r ecent values are even higher and comparable to those of liquid electrolytes.T otal ionic conductivities are heavily influenced by the synthesis method, grain boundary contributions,and methods used for conductivity measurements,i ncluding sintering cold-pressed pellets. [10] Solution-based Li 6 PS 5 Xs ynthesis routes typically give lower ion conductivities (10 À5 -10 À4 mS cm À1 ) [11][12][13] owing to phase impurities although recent studies using this method report high values for Li 6 PS 5 Cl and mixed anion Li 6 PS 5 (Cl,Br) argyrodites of 2.4 and 3.9 mS cm À1 ,r espectively; [14] and 3.1 mS cm À1 for Li 6 PS 5 Br.…”
mentioning
confidence: 80%
“…Many material classes are currently being investigated,s uch as oxides and phosphates, that is, the garnets [3,4] and NASICON (Na SuperIonic CONductor) materials, [5] as well as thiophosphates.I np articular,t he thiophosphates,f or example, Li 10 GeP 2 S 12 ,L i 6 PS 5 Xa nd Na 3 PS 4 ,a mong others, have shown to be promising materials due to the soft mechanical naturea nd the intrinsically highi onic conductivity. [6,7,[16][17][18][8][9][10][11][12][13][14][15] Typical approaches to attain even higher ionic conductivities within the respective classes involve either the use of aliovalent substitution to increase the number of mobile chargeso rt he introduction of softer,more polarizable anions and aconcurrent widening of the diffusion pathways. [19][20][21] Indeed,t he softer anion lattice with more polarizable anions has been corroborated to lower the activationb arrier, [22][23][24][25] thereby explaining the high ionic conductivity in many of the Li + and Na + conductingt hiophosphates.H owever,i th as re-cently been shown that as ofter lattice not only lowers the migration barrier,but also affects the entropy of migration, which can also lead to an overall lower ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%